Pengaruh Pembelajaran Kooperatif Tipe STAD Berbasis Etnomatematika Permainan Congklak terhadap Pemahaman Konsep Matematis Siswa - Yanti, Sri Hari; Nuh, Muhammad (Media Pendidikan Matematika, 2026)
This study aimed to examine the effect of the Student Teams Achievement Division (STAD) cooperative learning model integrated with ethnomathematics through the traditional congklak game on elementary school students’ mathematical conceptual understanding. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 36 fifth-grade students of SD Islam Kusumawardhana. The research instrument was a mathematical conceptual understanding test administered before and after the treatment. The results of the study showed that the experimental group achieved a higher mean posttest score of 82.78 compared to the control group, which obtained a mean score of 65.56. Based on the comparison between the pretest and posttest scores, the experimental group demonstrated an improvement of 32.50 points, whereas the control group showed an improvement of 15.84 points. The Independent Samples t-test revealed a significant difference between the experimental and control groups (t = 6.489, p < 0.05), with a Cohen's d value of 2.16, indicating a very large effect size. The t-test results indicated a significance value of 0.000 (< 0.05), demonstrating a statistically significant effect of the STAD learning model integrated with ethnomathematics through the congklak game on students’ mathematical conceptual understanding. Furthermore, the effect size value of 2.16 indicated a very large effect. Therefore, the STAD cooperative learning model based on the ethnomathematics of the traditional congklak game is effective in improving elementary school students’ mathematical conceptual understanding.